Aiaa Space 2016 2016
DOI: 10.2514/6.2016-5481
|View full text |Cite
|
Sign up to set email alerts
|

Space Assembly of Large Structural System Architectures (SALSSA)

Abstract: Developing a robust capability for Space Assembly of Large Spacecraft Structural System Architectures (SALSSA) has the potential to drastically increase the capabilities and performance of future space missions and spacecraft while significantly reducing their cost. Currently, NASA architecture studies and space science decadal surveys identify new missions that would benefit from SALSSA capabilities, and the technologies that support SALSSA are interspersed throughout the fourteen NASA Technology Roadmaps. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These decompositions were informed by several recent and historical ISA-related papers and studies. [7][8][9][10][11] The results of these evaluations contributed to development of a common nomenclature and a framework of assembly strategies, tasks, and capabilities that can be applied to meet the exploration challenges.…”
Section: On In-space Assemblymentioning
confidence: 99%
“…These decompositions were informed by several recent and historical ISA-related papers and studies. [7][8][9][10][11] The results of these evaluations contributed to development of a common nomenclature and a framework of assembly strategies, tasks, and capabilities that can be applied to meet the exploration challenges.…”
Section: On In-space Assemblymentioning
confidence: 99%
“…Subject to carrying capacity of a launch vehicle, these large space structures (LSSs) have to be constructed through on-orbit deployment or assembly. Recently, many researchers have pointed out that on-orbit assembly is the most likely solution to this issue with support from various technologies of space robots and modular structure designs (Dorsey and Watson, 2016;Duan, 2018;She et al, 2019;Wang and Hou, 2014). Some preliminary results (Boning and Dubowsky, 2010;Gong and Macdonald, 2019;Wang et al, 2019) have clearly demonstrated that undesirable vibration may be excited when constructing the LSS, significantly influencing its orbit and attitude motion.…”
Section: Introductionmentioning
confidence: 99%
“…This work is motivated by the problem of in‐space assembly of large structures using robotic assets. The need for constructing structures that are considerably larger than the mass and volume constraints of available launch vehicles has motivated NASA since the 1960s (Belvin et al., ; Dorsey & Watson, ; Komendera & Dorsey, ; Watson, Collins, & Bush, ). In particular, we perform experimental robotics to quantify and understand the feasibility of a recently proposed conceptual architecture for constructing large aperture telescopes where the primary mirror would be on the order of 100 m (Lee et al., ).…”
Section: Introductionmentioning
confidence: 99%